Law Education Based on Local Wisdom: Strengthening Laboratory Based Learning in Shaping the Legal Profession - Christina Wardhani, Lidya; Adi Surya, Faizal; Aryanto, Bayu (LPPM Universitas Jambi, 2026)
Legal education plays a strategic role in shaping a competent and just legal profession. However, the main challenge in Indonesia is the gap between graduates’ theoretical knowledge and practical readiness. This article analyzes the role of legal laboratory learning in addressing this challenge, while also exploring the relevance of integrating local wisdom into the process. This study employs a normative legal methodology with a legislative and conceptual approach, supported by empirical data from the Law Faculty Laboratory at Pasundan University and BANI Bandung, demonstrating that laboratory-based learning plays a crucial role in internalizing professional competencies. Through the laboratory, practical skills, professional ethics, and social sensitivity can be developed in an integrated manner. The integration of local wisdom has proven relevant for shaping legal professionals who are contextually grounded and responsive to the values of justice that are alive in society. Thus, strengthening local wisdom-based legal laboratory learning is an essential prerequisite for realizing legal professional education that is not only professional but also oriented toward social justice. This study demonstrates that integrating structurally embedded laboratory learning with local wisdom effectively prepares law graduates for modern practice. By bridging conceptual theory and empirical reality, this pedagogical model equips future legal professionals with crucial dispute resolution skills and acute social empathy.